2022
DOI: 10.21203/rs.3.rs-1794289/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Etiology analysis for full-term newborns with severe hyperbilirubinemia in eastern Guangdong

Abstract: Objective To explore the etiological characteristics of severe hyperbilirubinemia in full-term newborns of eastern Guangdong. Methods Full-term newborns with severe hyperbilirubinemia in one hospital from January 2012 to December 2021 were retrospectively analyzed. The etiology was determined according to the laboratory results and clinical manifestations. Results Among 1602 full-term newborns with hyperbilirubinemia in Chaozhou area, 32.20% (580/1602) was severe hyperbilirubinemia, including 213 newborns w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(18 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…The current reported that lower genotype rs4149056 frequencies, higher genotype rs2306283 frequencies, and higher genotype rs1805173 frequencies are associated with early onset severe hyperbilirubinemia in newborns. The results of genetic predictors for early onset severe hyperbilirubinemia in newborns of the current study are consistent with those of a case-control study on neonatal severe hyperbilirubinemia in Southeastern China, [5] a meta-analysis, [4] a retrospective analysis of neonatal severe hyperbilirubinemia in eastern Guangdong, China, [3] and a study on Indian neonatal hyperbilirubinemia. [13] Risk factors should be monitored, and clinicians should predict early onset severe hyperbilirubinemia in newborns and its treatment.…”
Section: Gene Locisupporting
confidence: 86%
See 4 more Smart Citations
“…The current reported that lower genotype rs4149056 frequencies, higher genotype rs2306283 frequencies, and higher genotype rs1805173 frequencies are associated with early onset severe hyperbilirubinemia in newborns. The results of genetic predictors for early onset severe hyperbilirubinemia in newborns of the current study are consistent with those of a case-control study on neonatal severe hyperbilirubinemia in Southeastern China, [5] a meta-analysis, [4] a retrospective analysis of neonatal severe hyperbilirubinemia in eastern Guangdong, China, [3] and a study on Indian neonatal hyperbilirubinemia. [13] Risk factors should be monitored, and clinicians should predict early onset severe hyperbilirubinemia in newborns and its treatment.…”
Section: Gene Locisupporting
confidence: 86%
“…The prevalence of early onset severe hyperbilirubinemia in the current study is consistent with that of available studies on African neonates [12] but is not consistent with a retrospective analysis of neonatal severe hyperbilirubinemia in eastern Guangdong, China. [3] Its prevalence is affected by environmental factors. [3] Hyperbilirubinemia in newborns is a global issue that requires identifying its cause and etiology.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations